(untitled) (Oratio Directa, 2023)
Among social scientists, the academic position of media studies, especially the position and function of print and electronic media, continues to be debated and develops dynamically. Academic perspectives range from positive views in the positivist media paradigm, through semi-critical post-positivist and constructivist paradigms, to critical and postmodernist or poststructuralist approaches. This qualitative study does not examine the postmodernist or poststructuralist paradigm. It analyzes the position and function of media from positivist, constructivist, and critical perspectives through a review of selected literature and documents. The study finds that constructivist and critical paradigms offer different perspectives, analytical depth, and levels of analysis for understanding the social, cultural, and ideological position and function of media compared with the positivist paradigm.